2005
DOI: 10.14358/pers.71.7.817
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Lidar-derived Elevation and Terrain Slope in Leaf-off Conditions

Abstract: The effects of land cover and surface slope on lidar-derived elevation data were examined for a watershed in the piedmont of North Carolina. Lidar data were collected over the study area in a winter (leaf-off) overflight. Survey-grade elevation points (1,225) for six different land cover classes were used as reference points. Root mean squared error (RMSE) for land cover classes ranged from 14.5 cm to 36.1 cm. Land cover with taller canopy vegetation exhibited the largest errors. The largest mean error (36.1 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
92
0
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 12 publications
(21 reference statements)
12
92
0
5
Order By: Relevance
“…Slope errors display little discernable pattern across the x-axis. Slope errors plotted by road grade did exhibit a slight tendency to under-predict surveyed slope at higher gradients, similar results were reported by Hodgson et al [53]. …”
Section: Lidar-derived Feature Accuracysupporting
confidence: 90%
See 1 more Smart Citation
“…Slope errors display little discernable pattern across the x-axis. Slope errors plotted by road grade did exhibit a slight tendency to under-predict surveyed slope at higher gradients, similar results were reported by Hodgson et al [53]. …”
Section: Lidar-derived Feature Accuracysupporting
confidence: 90%
“…In addition, the accuracy of road slope measurements was not significantly affected by increases in overhead canopy cover or road slope. A relatively small sample size was used for this analysis, though results fall in-line with previously reported values for forested areas [20,53]. While road grade measurements may be used with confidence, a host of other road characteristics are typically needed to accurately estimate road erosion.…”
Section: Discussionsupporting
confidence: 52%
“…WGEW is located within the San Pedro River basin, in a semi arid brush-grassland complex in the transition zone between Sonoran and Chihuahuan deserts [15]. The study area is a grass-dominated, small 1.91-ha watershed with an average slope of 9.4%.…”
Section: Study Areamentioning
confidence: 99%
“…The last return pulse is often considered the best estimate of the ground and is often assumed to be the -bald earth‖. However, even the last return will not necessarily be the ground as vegetation canopy may totally obscure the ground [15,16]. In addition, at small scales the utility of first and last return acquisition can be lost when the scanning device is stationary and the returns yield identical results do to the relative size of the footprint.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have also demonstrated that vegetation cover, terrain slope, and terrain variability can have a significant effect on elevation errors [21] [22] [23] [24] [25]. In general, elevation errors increase with vegetation cover and amount of understory as well as with increasing terrain slope and variability [26] [27] [28].…”
Section: Introductionmentioning
confidence: 99%